The Effect Of Social Media Marketing On Purchase Decisions With Brand Awareness As An Intervening Variables In Praketa Coffee Shop Purwokerto - Fajri, Ilham; Rizkyanfi, Mochamad; smaya, Rizma (Gastronomy Tourism Journal, 2021)
Culinary business is a sector that affects the growth of the tourism industry. As time goes by, the culinary business is growing fast, including in the city of Purwokerto where the intense competition between culinary business entrepreneurs is occurring. Praketa Coffee Shop Purwokerto must be able to develop and innovate to define the right marketing strategy. One of them is by using social media marketing to build consumer’s brand awareness, so that the purchase decision process will be built by itself. This research aims to discover the impact of social media marketing on the purchase decisions with brand awareness as an intervening variable at Ptraketa Coffee Shop Purwokerto. The type of research used is quantitative research with associative descriptive approach. The data collection technique used in this research is primary data, with method of distributing questionnaires to 100 respondents of Praketa Coffee Shop Purwokerto. The data analysis technique used Path Analysis regression and the Sobel Test. The results show that social media marketing has a positive and significant effect on brand awareness and on purchasing decisions, and brand awareness mediates positively and significantly on the relationship of between social media marketing and purchasing decisions.